On the localization and transport of specific adenoviral mRNA-sequences in the late infected HeLa cell. - Mariman, E (1982)
In the nucleus of HeLa cells late after infection with adenovirus type 2 mRNA-sequences which are processed via RNA splicing are attached to the nuclear matrix (Mariman et al., 1982). Although the mRNA, which codes for polypeptide IX, is not formed via splicing, about 70% of the non-polyadenylated pre-mRNA and the polyadenylated pIX mRNA are bound to the matrix structure, indicating that polyadenylation is performed while the RNA is associated with the matrix. Binding to the nuclear matrix seems to be a common property of all mRNA-sequences in the nucleus. At the late stage of infection most of the newly synthesized mRNAs which appear in the cytoplasm are viral specific (Beltz & Flint, 1979). Kinetic analysis of the newly synthesized poly(A)-containing mRNA on sucrose gradients reveals that 7-12 S messengers appear more rapidly in the cytoplasm than messengers larger than 13 S. More specifically, the nuclear exit time of the pIX-mRNA, which is the major 9 S adenoviral messenger late after infection, was determined to be about 4 min, while messengers transcribed from the late region 3 need more than 16 min to arrive in the cytoplasm. In the cytoplasm about 70% of the mRNA is bound to the cytoskeletal framework, while 30% remains as free mRNP. Analysis of the mRNA in both fractions reveals that L3-, E1B- and pIX-specific polyadenylated mRNA preferably exist as cytoskeleton-bound mRNA. However, significant differences occur in the partition of specific messengers over free and cytoskeletal RNA fractions.